INVESTIGATING THE PRACTICES AND STRATEGIC IMPLEMENTATION OF GREEN HUMAN RESOURCE MANAGEMENT IN ORGANIZATIONS - Aajaz Ahmad Hajam; Alphonsa S John; Shukurov Rustam Ergash O’g’li; Muyassar Raxmonova Abdufattohovna; Narziyeva Visola; Rakhmatullayeva Sogdiana (PT. Radja Intercontinental Publishing, 2024)
The accelerating pace of global industrialization has heightened the need for enhancing employee engagement, motivation, retention, brand value, and reducing labor turnover. Concurrently, increasing environmental risks and ecological imbalances have prompted stakeholders to urgently pursue environmental sustainability. Green Human Resource Management (Green HRM) has emerged as an innovative strategy that aligns human resource management with environmental sustainability. This study aims to elucidate the concept of Green HRM, its benefits, the policies and practices adopted by organizations, and the impact of Green HRM on traditional HR alternatives.